Budget Execution in Health Concepts, Trends and Policy Issues - Piatti-Funfkirchen, Moritz (The World Bank, 2021)
Most countries are commit ...
Keywords: Health Economics and Finance; Health Finance; Health, Nutrition and Population; Public Sector Development